Palatogenesis: The role of Sonic hedgehog (Shh) signaling in the secondary palate development - Elvan Şahin; Reem Al-towaitee (Sakarya Tıp Dergisi, 2022)
Palatogenesis is a complicated and precisely balanced process in which malfunctions induce congenital cleft palate, one of the most common embryonic developmental anomaly seen in newborns. Multiple signaling pathways and transcription factors have been implicated in palatal shelves development. The purpose of this article is to review one of the most important signaling pathways that plays a critical role in secondary palate development, namely Sonic hedgehog (Shh) signaling pathway. It includes an overview of the expression patterns of members of the Hedgehog signaling pathway and the role of Shh signaling in the reciprocal epithelial-mesenchymal interactions during secondary palate development.